Development of novel Gd-Fe/Ti composites with tunable thermal expansion property - Feng Xia; Xigang Yang; Yiye Yan; Minxian Liang; Yongchun Guo; Siyu Yang; Zhijun Ma; Chan Wang; Zhongwei Zhang; Qidi Zhou; Jilin Liu (Materials Research Express, 2024)
Titanium alloys are considered one of the most promising materials. However, their poor thermal expansion property remains a major obstacle to their widespread application. In this study, we explored an innovative design strategy to tune the thermal expansion properties of titanium alloy. Specifically, we used rare earth iron intermetallic compounds (Gd-Fe IMCs) with low coefficient of thermal expansion (CTE) as expansion inhibitors to prepare composites with the required thermal expansion properties via in situ reaction. The morphology and size of Gd-Fe IMCs can be effectively controlled by electromagnetic and ultrasonic fields, resulting in a dense distribution of micro/nano-structured Gd-Fe IMCs and strong interfacial bonding of the composites. This alloy has an excellent CTE of 6.8 × 10 ^−6 /K and a high ultimate tensile strength of 921 MPa. The improvement in the physical properties (especially in thermal expansion properties) of titanium alloy can be attributed to the synergistic effect between Gd-Fe IMCs and Ti matrix. This design strategy can also be extended to other titanium alloys as a reference for designing low thermal expansion titanium alloys.